Polyol-based Synthesis of Praseodymium Oxide Nanoparticles - Caroline Quievryn; Samuel Bernard; Philippe Miele (Nanomaterials and Nanotechnology, 2014)
A series of well-crystallized praseodymium oxide (Pr6O11) nanoparticles are synthesized via a highly scalable process from praseodymium nitrate. Praseodymium hydroxide is synthesized through a modified polyol process and subsequent calcination in air at 600°C for 2 h to transform the precursor material into Pr6O11 nanoparticles. A complete characterization of a specific sample by SEM, HRTEM, and X-ray diffraction (XRD) demonstrates that Pr6O11 nanoparticles form elementary blocks with a calculated size of 118 nm, containing slightly agglomerated nanocrystalline particles with a polycrystalline face-centred cubic phase and an individual size of around 10 nm. Particles can be easily dispersed in water through ultrasonification. Particles display a BET Specific Surface Area (SSA; 8.75 m² g-1) with a nitrogen adsorption-desorption isotherm of type II and a helium density of powders (d = 5.66 g cm-3).